AN ANALYSIS OF DRUG INVENTORY CONTROL EFFICIENCY USING ALWAYS BETTER CONTROL, VITAL ESSENTIAL NON-ESSENTIAL, AND ECONOMIC ORDER QUANTITY METHODS: A CASE STUDY AT ASSALAAM MEDICARE - Arief, Khunaisa; Nafisah, Umi; Amalia, Annora Rizky (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
In-depth control of pharmaceutical inventory is critical, especially in healthcare facility units to ensure the availability of drugs to minimize the risk of stagnation (excess inventory of drugs) and inventory vacancies (shortage or empty level of inventory). The purpose of this study is to determine how inventory level control is carried out at Assalaam Medicare pharmacy using the ABC (Always, Better, Control), VEN (Vital, Essential, Non Essential), and EOQ (Economic Order Quantity) methods for the period January to March 2024. Based on ABC analysis of a total of 572 items of drugs, 151 items of drugs are classified into group A which accounts for 27.970 or 65%, with an investment value of 75% of the total, group B with 215 drug items with a consumption of 10,236 or 24% and an investment of 20%, and group C with 206 items which has a consumption of 4,521 or 11% and an investment of 6%. From the VEN analysis, 26 drug items belong to the vital (V) drug class of group A as an essential service segment. According to EOQ, the highest optimum order quantity is 2.061 items and the lowest optimum value is 17 items for a single order.